The Jewish Role in American Life An Annual Review (Purdue University Press, 2007)
The relationship between Jews and the United States is necessarily complex: Jews have been instrumental in shaping American culture and, of course, Jewish culture and religion have likewise been profoundly recast in the United States, especially in the period following World War II. A major focus of this work is to consider the Jewish role in American life as well as the American role in shaping Jewish life. This fifth volume of the Casden Institute's annual review is organized along five broad themes-politics, values, image, education and culture.